If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+5=2x+27
We move all terms to the left:
3x+5-(2x+27)=0
We get rid of parentheses
3x-2x-27+5=0
We add all the numbers together, and all the variables
x-22=0
We move all terms containing x to the left, all other terms to the right
x=22
| 4x-16=12x+8 | | -4w^2-13w-3=0 | | 4-6n=58 | | 16u+u-16u=15 | | 10b-16=84 | | (5x+15°)=(4x-6) | | 76+36=14x-2 | | (5x+15°)=(4x-6°) | | x-39=3/4-x | | 17-14k=-7-6k | | 3x+3=2/3 | | |3x-4|=10 | | 4y-10=2y-12 | | 8×(3-x)=x+25 | | 7b-b-2b-b=12 | | 10g+4g-13g+2g+2g=15 | | (43x+36)+(54x+14)=180 | | 10x-9=4x+37 | | 10g+4g-13g+2g=15 | | T=p+18 | | 35+0.20x=98 | | 4b+3b-b=6 | | 5x-37=300 | | 13s-10s=18 | | 6=7y-3 | | 6(d+2)=18 | | 5w-4w=18 | | -22x-132=-44 | | 19d+d=20 | | -7b+6=-2b+1 | | 17=c+2 | | 20m-19=16 |